Host condition and individual risk of cowpox virus infection in natural animal populations: cause or effect? - Beldomenico, Pablo Martín (2009)
Recent studies have provided evidence that endemic pathogens may affect dynamics in animals. However, such studies have not typically considered that infected individuals might have a preceding underlying poor condition. We examined whether individuals in poor condition are more likely to become infected by an endemic pathogen, using as a system the dynamics of cowpox virus in field voles. With data from monthly sampled vole populations, a nested case-control study evaluated whether susceptible individuals with poorer condition had higher probabilities of contracting cowpox. The influence of condition was found to be considerable, especially for males. At times when a susceptible male with good body condition had a relatively low probability of becoming infected, a susceptible male with poor body condition was twice as likely to contract cowpox; if this male was also anaemic, the chances were almost quadrupled. We discuss the care needed when interpreting the findings of wildlife disease studies.